2015
DOI: 10.1021/acs.jmedchem.5b00958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Homobivalent Carbolines as Designed Multiple Ligands for the Treatment of Neurodegenerative Disorders

Abstract: Neurodegenerative diseases represent a challenge for biomedical research due to their high prevalence and lack of mechanism-based treatments. Because of the complex pathology of neurodegenerative disorders, multifunctional drugs have been increasingly recognized as potential treatments. We identified homobivalent γ-carbolinium salts as potent inihitors of both cholinesterases, N-methyl-D-aspartate receptors, and monoamine oxidases. Homobivalent γ-carbolines displayed similar structure-activity relationships on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Surprisingly, curcumin and ferulic acid were found to inhibit hMAO-A selectively, whereas the F I G U R E 3 7 γ-Carbolines (55, 56a-e, 57a-h, and 58a-e). 177 which was lower than that of selegiline (K i = 0.13 ± 0.09 µM). Further, a gradual shift was observed from hMAO-B selectivity (61a, 61b) to nonselectivity (61c-f) as there was an increase in chain length at the amino terminus.…”
Section: Ferulic Acid Amidesmentioning
confidence: 69%
See 3 more Smart Citations
“…Surprisingly, curcumin and ferulic acid were found to inhibit hMAO-A selectively, whereas the F I G U R E 3 7 γ-Carbolines (55, 56a-e, 57a-h, and 58a-e). 177 which was lower than that of selegiline (K i = 0.13 ± 0.09 µM). Further, a gradual shift was observed from hMAO-B selectivity (61a, 61b) to nonselectivity (61c-f) as there was an increase in chain length at the amino terminus.…”
Section: Ferulic Acid Amidesmentioning
confidence: 69%
“…Otto et al identified homobivalent γ‐carbolines ( 55 , 56a ‐ e , 57a ‐ h , and 58a ‐ e ) as potent inhibitors of MAO‐B, thereby presenting promising ligands for the treatment of NDDs (Figure ). The bivalent γ‐carbolines displayed inhibitory activities against MAO‐B, with IC 50 values in the micromolar to submicromolar range.…”
Section: Discovery and Development Of Mao‐b Inhibitors (2015‐2018)mentioning
confidence: 99%
See 2 more Smart Citations
“…A significant number of carbolines have been exploited for diverse pharmaceutical applications. Some γ‐carbolinium salts are found to be potent inhibitors of cholinesterases, N ‐methyl‐D‐aspartate receptors, and monoamine oxidases . Harmine, a β‐carboline, has been identified as an inhibitor of DYRK family of kinases .…”
Section: Introductionmentioning
confidence: 99%